Optimum light intensity for larval rearing of African catfish, Clarias gariepinus - Sanudin , Noorsyarinah; Tuzan, Audrey Daning; Mukai, Yukinori (2012)
African catfish, Clarias gariepinus is one of the most popular species that being cultured in the world. The advantages to grow rapidly in high density, in poor water quality with good taste make African catfish becoming more important in Africa and Asia finfish culture. However, the major problem of culturing African catfish is the cannibalism. Cannibalism has caused low survival rate and yield high mortality. Preliminary study showed that continuous darkness and dim light conditions were the best due to the natural habit of this species which is nocturnally active